Advanced electric drive vehicles - Emadi, Ali (Boca Raton : CRC Press, 2015)
"Preface Electrification is an evolving paradigm shift in the transportation industry toward more efficient, higher performance, safer, smarter, and more reliable vehicles. There is in fact a clear trend to shift from internal combustion engines (ICEs) to more integrated electrified powertrains. Non-propulsion loads, such as power steering and air-conditioning systems, are also being electrified. Electrified vehicles include more electric vehicles (MEVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), range-extended electric vehicles (REEVs), and all electric vehicles (EVs) including battery electric vehicles (BEVs) and fuel cell vehicles (FCVs). This book begins with an introduction to the automotive industry and explains the need for electrification in Chapter 1. Parallels with other industries such as the telecommunications industry are highlighted. Chapter 1 also explains how the paradigm shift began with MEVs, was established by HEVs, is gaining momentum by PHEVs and REEVs, and will be completed by EVs. Chapters 2 and 3 present the fundamentals of conventional vehicles and ICEs, respectively. Chapters 4 through 7 focus on the major components of electrified vehicles including power electronic converters, electric machines, electric motor controllers, and energy storage systems. Chapter 8 introduces hybrid battery/ultra-capacitor energy storage systems with applications in advanced electric drive vehicles"--
Bibliografija nakon svakog poglavlja.
Keywords: Electric vehicles; TECHNOLOGY & ENGINEERING / Electronics / General; TECHNOLOGY & ENGINEERING / Mechanical